Peran Masyarakat Dalam Penyelenggaraan Perlindungan Anak Menurut Undang-Undang Perlindungan Anak - Deshaini, Liza (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2022)
Protection of children is all activities to guarantee and protect children and their rights so that they can live, grow, develop, and participate optimally in accordance with human dignity and protection from violence and discrimination. The role of the community in the implementation of child protection is carried out by providing information through socialization and education regarding children's rights and laws and regulations regarding children, providing input in the formulation of policies related to child protection, reporting to the authorities in case of violations of children's rights, taking an active role in the process. rehabilitation and social reintegration for children, monitoring, supervising and taking responsibility for implementation of child protection, providing facilities and infrastructure as well as creating a conducive atmosphere for children's growth and development, playing an active role by eliminating negative labeling of child victims, providing space for children to be able to participate and express opinions and legal consequences against perpetrators who treat children discriminatory so that children experience material, moral and social losses are punishable by a maximum imprisonment of 5 (five) years and/or a maximum fine of Rp. 100,000,000.00 (one hundred million rupiah).